Estado de conservación, del aceite impregnado en hojuelas de Solanum tuberosum de marca comercial, que se consumen en la ciudad de Trujillo - Jara Aguilar, Demetrio Rafael (2020)
In this research we studied, framed in the area of food toxicology the "State of conservation of oil impregnated in flakes of Solanum tuberosum, trademark, which are consumed in the city of Trujillo." For the study, 50 samples acquired in the same number of commercial establishments of the main streets of the city 's Enclosure were used. The technique used consisted in measuring the Oxidability Index of the oil impregnated in each sample. After the analysis of the results, it was concluded that 100% of the samples sold in all commercial establishments are not suitable for human consumption